Optimalisasi kemampuan komunikasi matematis siswa dengan model discovery learning - Yani, Merisa Yayu Mutiara Ibay; Hendriana, Heris; Chotimah, Siti (IKIP Siliwangi, 2024)
The aim of this study was to look at the improvement in mathematical communication skills of eighth-grade students who used the discovery learning model with eighteenth-year-olds who used conventional models. The experimental quota method used in the research this time. The research subjects involved two classes VIII of SMP Negeri 1 Cihampelas, in which one class applied the discovery learning model VIII-1 and the other class using conventional learning VIII-5. The data in this study is obtained from five tests on the description of mathematical communication abilities. The research data is derived from the results of pretes and postes and then processed with the test of data normality, test of homogenity of variance, and test of significance of difference 2 averages using the help of IBM SPSS Statistic 27 software. The results of the study showed that the improved mathematical communication skills of eighth-grade students who used the discovery learning model were better compared to eighteenth-year-olds who used conventional models. Thus, the discovery learning model can be used as an alternative to the application of mathematics in the learning process to improve students' mathematical communication skills.